Evaluating the impact of nano-magnesium calcite waste on the performance of cement mortar in normal and sulfate-rich media. (10th April 2019) - Abdel-Gawwad, H.A.; Heikal, Mohamed; Mohammed, Mona S.; El-Aleem, S. Abd; Hassan, Hassan Soltan; García, S.R. Vásquez; Rashad, Alaa M.
Highlights: Urea and urease enzyme were used for the removal of Ca 2+ and Mg 2+ from ground water. Nano-magnesium calcite (NMC) waste is a byproduct of ground water treatment. NMC was mixed with cement mortar to enhance its engineering properties and durability. NMC showed a positive effect on the performance of cement mortar in sulfate medium. Abstract: The motivation behind this work is to evaluate the impact of nano-magnesium calcite (NMC) waste on the performance of cement mortar (CM) and its resistivity to sulfate attack. The addition of urea and urease enzyme to ground water resulted in the removal of Ca 2+ and Mg 2+ as NMC precipitate (byproduct of treatment process). As a beneficial recycling method, NMC with different proportions were individually blended with CM to enhance its performance in normal and sulfate-rich media. The results revealed that the NMC has a positive impact on the early-ages compressive strength of CM. Where, the addition of 1 wt% of NMC led to a significant enhancement in the rates of strength development and total porosity reduction at all ages of hydration. Comparing with reference mixture, a highest performance in sulfate medium was obtained in case of all CMs containing NMC. Complementary, the CM incorporated with 1 wt% NMC showed the highest resistance to sulfate attack (up to 12-months) which associated with lower compressive strength regression, total porosity increment, sulfate expansion and consequently lower ettringite formation rate.